Smart robotic mobile fulfillment system with dynamic conflict-free strategies considering cyber-physical integration. (October 2019) - Lee, C.K.M.; Lin, Bingbing; Ng, K.K.H.; Lv, Yaqiong; Tai, W.C.
Highlights: A two-stage decoupled algorithm for conflict-free routing is proposed. Different types of collisions are detected by time window. The A* algorithm is improved to generate possible paths at one time. Abstract: Smart mobile robots are deployed to the warehouse environments to improve the efficiency, because of its characteristics of high automation and flexibility characteristics. However, the trajectory planning is a great challenge especially when a number of mobile robotics operates in the warehouse simultaneously. This paper proposes a cyber-physical system model for smart robotic warehouse to implement the workflow data collection and procedure monitor. A decoupled method is presented to find a conflict-free path for the mobile vehicles in the warehouses, after distributing destinations to mobile robots to minimize the total travel distance. The improved A* algorithm is applied to find paths from the source node to the destination node for single mobile vehicle in the domain of smart logistics. Collisions are detected by comparing the occupying time window of each mobile vehicle. Three collision avoidance strategies are developed to solve the conflicts and the candidate path with the minimal completion time is selected as the final determined route. The contribution of the paper is to propose a CPS-enabled robotic warehouse with dynamic conflict-free strategy to self-configure the path to optimize warehouse operation efficiency.